A chronic epidemic of hysterical blackouts in a comprehensive school. Issue 6320 (27th March 1982) - Mohr, P D; Bond, M J
Abstract : An epidemic of hysterical blackouts in a modern comprehensive school affected 60 teenage girls and three boys, who from September 1978 to June 1980 had a total of 447 blackouts. The chronic nature of the epidemic was unusual, and several reasons for this emerged. The visible impact of the epidemic was diluted by the large size of the school and because affected pupils used general-practitioner services and hospital departments in the neighbourhood. As a result, eight received inappropriate treatment for epilepsy, and this may have helped to establish the behaviour pattern within the school. In addition, a small core of eight girls with a high incidence of behaviour and family problems were repeatedly affected and may have acted as triggers for new cases. Once medical supervision was centered on one neurology outpatient clinic the epidemic gradually resolved.